Interactions between Loci Contributing to Antimicrobial Resistance and Virulence in Neisseria gonorrhoeae - Tatum D. Mortimer (mBio, 2022)
ABSTRACT In a recent mBio article, Ayala et al. (mBio 13:e00276-22, 2022, https://doi.org/10.1128/mbio.00276-22) identified a single nucleotide variant in the repressor gdhR in Neisseria gonorrhoeae that reduces binding to the promoter of the virulence factor lctP and thereby increases its expression. The allele (gdhR6) frequently co-occurs with mutations in the mtr operon promoter that reduce expression of another repressor, mtrR, resulting in overexpression of the efflux pump-encoding mtrCDE and increased antimicrobial resistance. Because mtrR also represses gdhR, a decline in mtrR would decrease expression of lctP. Hypothesizing that gdhR6 arose to circumvent the impact of mtrR promoter mutations on lctP expression, the authors analyzed these loci in genomes of N. gonorrhoeae isolates from the preantibiotic era. Surprisingly, they found isolates with gdhR6 prior to selection for mtrR resistance-associated alleles. These results suggest that independent and perhaps interacting pressures have influenced the co-occurrence of these alleles.